Numerical analysis of integrated photonics structures for hemoglobin sensor application - Struk, Przemysław (Photonics Letters of Poland, 2020)
This paper presents sensor structure dedicated for determination the key properties of blood – concentration level and oxidation level. The sensor structure is based integrated optics circuit with diamond-based planar waveguide including prism and grating coupler. The paper is focused on numerical analysis of selected properties of sensor structure for optimization sensing parameters. Full Text: PDF References D.A. Gell, Blood Cells, "Structure and function of haemoglobins", Molecules and Diseases 70 (2018). CrossRef I. Singh, A. Weston, A. Kundur, G. Dobie, Haematology Case Studies with Blood Cell Morphology and Pathophysiology (Elsevier: Amsterdam, The Netherlands, 2017) DirectLink P. D. Sturkie, P. Griminger, Blood: Physical Characteristics, Formed Elements, Hemoglobin, and Coagulation Avian Physiology (Springer-Verlag New York Inc. 1976). CrossRef A. Dutta, B. Deka, P.P. Partha, Planar Waveguide Optical Sensors: From Theory to Applications (Springer: Berlin, Germany, 2016). CrossRef S. Kang, K. Sasaki, H. Minamitani, "Determining the absorption coefficient of hemoglobin derivatives with integrated optic waveguide sensor", IEEE Engineering in Medicine and Biology Society (1992). CrossRef P. Struk, "Design of an Integrated Optics Sensor Structure Based on Diamond Waveguide for Hemoglobin Property Detection", Materials 12(1) 175 (2019). CrossRef W. Lukosz, K. Tiefenthaler, "Sensitivity of integrated optical grating and prism couplers as (bio)chemical sensors", Sensors and Actuators 15 (1988). CrossRef P.V. Lambeck, "Integrated optical sensors for the chemical domain", Measurement Science and Technology - IOPscience 17 (2006), CrossRef W. Lukosz, "Integrated optical chemical and direct biochemical sensors", Sensors and Actuators B: Chemical 29 (1995). CrossRef P. Struk, T. Pustelny, K. Gołaszewska, E. Kamińska, M. Borysiewicz, M. Ekielski, And A. Piotrowska, "Photonic structures with grating couplers based on ZnO", Opto−Electronics Review 19(4) (2011). CrossRef J. Haas, E. V. Catalán, P. Piron, F. Nikolajeff, L. Österlund, M. Karlsson, B. Mizaikoff, "Polycrystalline Diamond Thin-Film Waveguides for Mid-Infrared Evanescent Field Sensors", ACS Omega 3 (2018). CrossRef P. Struk, "Design of an integrated optics sensor structure for hemoglobin property detection", Proceedings of SPIE 11204 (2019). CrossRef P. Struk, T. Pustelny, K. Gołaszewska, E. Kamińska, M. Borysiewicz, M. Ekielski, A. Piotrowska, "Hybrid photonics structures with grating and prism couplers based on ZnO waveguides", Opto-Electronics Review 21 (2013). CrossRef V. Prajzler, M. Varga, P. Nekvindova, Z.; Remes, A. Kromka, "Design and investigation of properties of nanocrystalline diamond optical planar waveguides", Optics Express 21 (2013), CrossRef E.N. Lazareva, V.V. Tuchin, "Measurement of refractive index of hemoglobin in the visible/NIR spectral range", Journal of Biomedical Optics 23 (2018). CrossRef Optiwave Systems Inc. "OptiFDTD Technical Background and Tutorials - Finite" (2013). DirectLink K. Yee, Antennas and Propagation, "Numerical solution of initial boundary value problems involving maxwell's equations in isotropic media", IEEE Transactions 14,3 (1966). CrossRef